Motivasi Orangtua Siswa dalam Memilih Sekolah TK IT Wihdatul Ummah Makassar - Muhammad Afdal (Concept: Journal of Social Humanities and Education, 2023)
The type of research used aims to determine the motivation of parents of students in choosing a TK IT Wihdatul Ummah Makassar school. This research was carried out in December 2021. The research method used was field research with a qualitative approach. The data collection technique is the interview technique. The research instruments used were field observations, interviews and documentation. The number of respondents taken was 25 people who were parents of students at TK IT Wihdatul Ummah Makassar. The results of research conducted by researchers through interviews show that the motivation of parents of students in choosing the IT Wiihdatul Ummah Makassar Kindergarten school by considering the quality of education provided where the school provides a portion of learning according to the abilities and age of children who tend to play in accordance with the teachings of the Qur'an ’an and Sunnah. In addition, parents also chose the school because the communication that exists between teachers and parents is very smooth and parents are also given special programs to improve and increase religious knowledge.